FENOMENA NIKAH MUT’AH SEBAGAI UPAYA LEGALISASI PENYALURAN NAFSU SEKSUAL DIBALIK PERNIKAHAN PERMANEN - Suaidi Suaidi (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Sexual channeling can only be done through marriage, like ordinary marriage, milkul yamin, or mut'ah. All three systems of sexual marriage are recognized as egalized by Islamic law. Because milkul yamin is more inclined to slavery, its legalization has long been extinct because it tends not to put women's rights and honor in a priority position. While mut'ah marriage is still used as an alternative choice in efforts to channel men's sexual appetite, it is not possible to have ordinary marriages due to certain factors. However, mut'ah marriage is still debated among jurists because of certain times, such as one week, one month and one year. The phenomenon that occurs among the community makes mut'ah marriage as a choice of the validity of the distribution of sexual appetite within a certain time according to the agreement of both parties in determining the time of the end of mut'ah marriage. However, if within that certain period of time, the mut'ah couple has children, then the problem is, who is responsible for the life of the child when the agreed time has been completed. Therefore, although mut'ah marriage is legally recognized, however, problems tend to arise that lead to the abandonment of children resulting from mut'ah marriage